Urgensi Membangum Budaya Literasi Islam Di Perguruan Tinggi Umum - Nurhilaliyah; Amri Rahman (CV. SINAR HOWUHOWU, 2026)
The culture of Islamic literacy in General Higher Education (GHE) institutions faces significant challenges in the digital transformation era, where students tend to rely on instant online information with questionable academic validity. This study aims to examine the urgency of developing a critical and moderate Islamic literacy culture to strengthen students’ Islamic identity amidst the advancement of modern science. This research employs a qualitative approach using a library research method, with data collected from scientific literature and analyzed through content analysis techniques. The findings indicate that Islamic literacy extends beyond the ability to read religious texts, encompassing analytical, evaluative, and contextual application skills in daily life. The low level of literacy culture is influenced by predominantly theoretical learning methods and the lack of critical dialogue. Therefore, integrated efforts are required, including curriculum strengthening, the use of credible academic digital platforms, and the development of literacy-based learning to produce students who are not only academically competent but also possess strong moral character and critical thinking skills.